The Use and Misuse of Evidence - O'Hara, Amy (International Journal of Population Data Science, 2026)
Objective Over the past decades, the US has developed plans and refined methods to use data for evidence-building. Administrative data linkages feature prominently in evaluations to determine which policies are working (and which are not). In the past, analysts, policymakers and administrators worried about data access and quality. They also faced obstacles discovering relevant evidence and knowing how to translate evidence into action. These challenges pale in comparison with events in the US over the past 18 months, as Trump Administration policy pronouncements ignored evidence and abused facts and science. Approach In this paper, we describe the evidence infrastructure in the US before and after Trump’s second term. We review successes in certain domains and challenges in others, with a focus on data sources and data integrity. Results We share qualitative and quantitative information about the state of evidence building and use, noting impacts on science, funding, talent pipelines, and government measurement capabilities. We also share observations from convenings of data experts, policymakers, program administrators, technologists, and researchers who participated in Evidence & Incentives (E&I) Group convenings. The E&I group was founded in 2024 by North American researchers and former government officials studying the incentives and disincentives of evidence building. Conclusion We present recommendations to (a) focus policymaker, public, and media attention on norms involving evidence, (b) demand transparency and accountability when officials cite flawed evidence, and (c) track and remedy the disruption in investments in scientific knowledge and research.